Cash waqf as a solution of food need problem in Indonesia - Hanesti, Elsi Mersilia; Kurnia, Riana Aflika Eka; Herianingrum, Sri (MEC-J (Management and Economics Journal), 2018)
Price rise and scarcity of food become the main root of the economic problems in Indonesia Both goverment and whole society in each level intervene to resolve this problem. Then, how effective is the solution to overcome the problems of agriculture and animal husbandry in Indonesia? With the method of writing and literature study conducted in-depth analysis with ilustration model, the authors found that the application of cash waqf in the development of agriculture and animal husbandry in certain regions in Indonesia can help to solve the problem of the fulfillment of food needs of Indonesian society. With this concept, every region in Indonesia can increase their agriculture and animal husbandry potential output (quality and quantity). Subsequent impact and the expected development of the real sector are that every region in Indonesia can distribute their agriculture and animal husbandry potential output to meet the food needs of Indonesian society as a whole, minimize the need for food shortage, build society welfare, and increase GDP, followed by rising national income.